Asiaticoside ameliorates type 2 diabetes mellitus in rats by modulating carbohydrate metabolism and regulating insulin signaling - B. Prathap; V. Satyanarayanan; K. Duraipandian; P. Subashree (Asian Pacific Journal of Tropical Biomedicine, 2024)
Objective: To evaluate the effect of asiaticoside on streptozotocin (STZ) and nicotinamide (NAD)-induced carbohydrate metabolism abnormalities and deregulated insulin signaling pathways in rats. Methods: Asiaticoside (50 and 100 mg/kg body weight) was administered to STZ-NAD-induced diabetic rats for 45 days, and its effects on hyperglycaemic, carbohydrate metabolic, and insulin signaling pathway markers were examined. Results: Asiaticoside increased insulin production, lowered blood glucose levels, and enhanced glycolysis by improving hexokinase activity and suppressing glucose-6-phosphatase and fructose-1,6-bisphosphatase activities. Abnormalities in glycogen metabolism were mitigated by increasing glycogen synthase activity and gluconeogenesis was decreased by decreasing glycogen phosphorylase activity. Furthermore, asiaticoside upregulated the mRNA expressions of IRS-1, IRS-2, and GLUT4 in STZ-NAD-induced diabetic rats and restored the beta cell morphology to normal. Conclusions: Asiaticoside has the potential to ameliorate type 2 diabetes by improving glycolysis, gluconeogenesis, and insulin signaling pathways.